Public bus level of service performance in Peninsular Malaysia: Correlation analyses on level of service (LOS) and passengers' satisfaction level - Ponrahono, Zakiah; Bachok, Syahriah; Mohamed Osman, Mariana; Ibrahim, Mansor; Abdullah, Muhammad Faris (Malaysian Institute of Planners, 2017)
This study explore the stage bus performance of 48 routes within selected urban and regional settlements in Peninsula Malaysia, using a quantitative traffic engineering measure known as Level of Service standards or LOS and validated through the evaluation of passengers' satisfaction level. The findings on the level of service (LOS) highlight the poor performance of the urban and rural bus service with the tolerable threshold below D. There are clear disparities on LOS and passenger satisfaction level between the urban and rural bus operation systems in terms of frequency, operation hour, bus speed, and passengers' load threshold.